Why so Touchy? Navigating Physical Touch in the Performing Arts - Joseph Skillen; Gretchen Alterowitz; Michelle Reinken (Academic Chairpersons Conference Proceedings, 2023)
Physical touch is endemic to instruction in the Performing Arts. Two Performing Arts Chairs and the University’s Title IX Coordinator share approaches and solutions to navigating challenges resulting from the use of touch in student-instructor interactions.
Keywords: Title IX; Physical Touch; Consent; Music; Dance; Performing Arts